(untitled) (Bangladesh Journal of Pharmacology, 2019)
This study aimed to investigate the anti-tumor effects of compound 34 on MCF-7 cells in vitro, and explore its mechanisms. MTT results showed that compound 34 selectively inhibited estrogen receptor-positive cells proliferation. Hoechst 33342 staining showed nuclear pyknosis, nuclear debris associated with apoptotic bodies. JC-1 staining showed the loss of mitochondrial membrane potential. Although compound 34 increased intracellular reactive oxygen species (ROS), compound 34-induced apoptosis was not prevented by pretreatment with ROS scavengers. Western blotting showed apoptosis-related protein like cytochrome c and cleaved PARP protein increased. Furthermore, docking studies exhibited that compound 34 could bind into ERα. In summary, compound 34 selectively inhibited estrogen receptor positive cells proliferation and induced apoptosis in MCF-7 cells via ROS-independent intrinsic apoptosis in MCF-7 cells. It may be a potential targeted drug of estrogen receptor for therapeutic application of breast cancer. Video Clip of Methodology: Assay of Cell Proliferation: 5 min 5 sec Click to watch